Perverse outcomes from fencing fauna: Loss of antipredator traits in a havened mammal population. (May 2023) - Harrison, Natasha D.; Phillips, Ben L.; Mitchell, Nicola J.; Wayne, Julia C.; Maxwell, Marika A.; Ward, Colin G.; Wayne, Adrian F.
Abstract: Populations of threatened animals are increasingly preserved within predator-free havens, where populations tend to grow rapidly, resource competition increases, and traits relevant to avoiding predation may be selected against. We examine this phenomenon using a ten-year longitudinal dataset on a threatened Australian mammal; the woylie ( Bettongia penicillata ogilbyi ). Behavioural and morphological data were collected during routine monitoring of a havened woylie population and an adjacent wild population where predators occur, from which six traits relating to predator escape were extracted. Paired comparisons revealed that havened woylies were less likely to show injuries from excessive agitation in traps, were less likely to eject pouch young, and had shorter approach distances compared to woylies outside the haven, suggesting a dampened antipredator response. Further, body mass and relative leg length declined over time in the havened population, compared with no change outside of the haven, suggesting selection in the haven against body size. Population density affected body size and agitation in traps differently in havened and non-havened populations, indicating an interaction between resource competition and relaxed selection that likely hastens the loss of anti-predator traits. Our study offers a mechanistic understanding of the loss of anti-predator responses in havens, which is essential for guiding how populations could be managed to better realise their potential for recovering threatened fauna.